ANALYSIS OF SUPPLY AND DEMAND OF TOURISM PRODUCTS IN SANUR BEACH BALI - Ridla, Muhammad; Sawu, Michael Rudolfus (Tourism Department, State Polytechnic of Banyuwangi, 2024)
Supply and demand are vital aspects in the development of the tourism sector. Comprehensive considerations will greatly determine the direction of the development of the tourism sector. This study aims to analyze the components of tourism products, tourism supply, and demand at Sanur Beach. Qualitative research with a descriptive qualitative approach was used in this study. The in-depth research method involved informants such as tourism managers, tourists, and other tourism practitioners at Sanur Beach. The data analysis method used was qualitative description. This study found that the provision of tourism product components, supply, and demand are categorized as good. However, it is necessary to maintain and improve their development in the future. The implication of this research is to enhance the development of supply and demand in order to improve the quality of tourism products. This study contributes to the discourse on the development of coastal tourism attractions.